Strengthening coastal teachers’ career guidance capacity through digital module training: A training of trainers approach - Hasanah, Afifah Nur; Asrila, Agitia Kurniati; Rahmi, Iftita; Hidayati, Izzanil; Rahayu, Wirza Feny; Juwita, Silvia; Deri, Putri Sukma; Dalimunthe, Hanifa Laura; Guspa, Anindra; Irta, Aflah Zakinov; Susanti, Roza Eva (Community Empowerment, 2025)
High school graduates in Indonesia's coastal areas, including Agam Regency, face high unemployment rates due to limited access to career information and curriculum gaps. This community service program aims to strengthen the capacity of teachers at SMAN 1 Tanjung Mutiara in providing career guidance through digital module-based training using a Training of Trainers (ToT) approach. Twenty-two teachers participated in the training, which was evaluated using the Kirkpatrick model at the reaction and learning levels. The results indicated high participant satisfaction regarding the training materials and facilities. Furthermore, 81% of participants showed an increase in knowledge, supported by the Wilcoxon signed-rank test results showing a significant statistical increase (p < .001). The success of this program proves that digital module-based teacher training is effective in enhancing students' career readiness and expanding access to higher education in coastal regions.